If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3q + 9 = -18 Reorder the terms: 9 + -3q = -18 Solving 9 + -3q = -18 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -3q = -18 + -9 Combine like terms: 9 + -9 = 0 0 + -3q = -18 + -9 -3q = -18 + -9 Combine like terms: -18 + -9 = -27 -3q = -27 Divide each side by '-3'. q = 9 Simplifying q = 9
| -2x(x+3y)=18 | | 4x*2-9=0 | | 4xy+2x+6y+3=0 | | (y-5)-(y+7)=8y | | X-26=4 | | 4q=92 | | 3t-3=9+9t | | 5c+12=7c+11.84 | | 10x+x^2=84 | | -3x-30x-75=0 | | -10y^2-4(5y^2-8)+6y= | | -x^2-4x=-47 | | -5+8(x-3)=17x+2-9x | | -x^2-4x= | | 18=0.2x+5 | | -3(-7-6n)=-11+2(4+5n) | | 52+14m=318 | | -9+10=m-9 | | 10x-4=6x+2 | | 7x+10=-60-7x | | 7x+10=-60-7x | | 2m+14-5(m-1)=9m-(5m-4)-8m+9 | | (6+x)*(10+x)=144 | | m^2-14+49=0 | | 33n-195=234 | | mx^2+(2m+3)x+(m-1)=0 | | -9m+51-9(m-3)=3m-(4m-4)-2m+1 | | 7x+17=52 | | 8+2n=20 | | 7+3n=19 | | 2y-6=5x+8 | | 9(r+8)= |